The Heckscher-Ohlin Theorem in the Multi-Commodity Case - Bhagwati, Jagdish N. (Journal of Political Economy, 1972)
The article focuses on the Heckscher-Ohlin theorem in the multi-commodity case. Economist Ronald Jones, in his seminal paper on Heckscher-Ohlin theory, has argued that for the case of two countries, two factors and several commodities, the Heckscher-Ohlin theorem would certain valid in the following weak sense: "Ordering the commodities with respect to the capital-labor ratios employed in production is to rank them in order of comparative advantage. Demand conditions merely determine the dividing line between exports and imports, it is not possible to break the chain of comparative advantage by exporting, say the third and fifth commodities and importing the fourth when they are ranked by factor intensity" Furthermore, as Jones had pointed out if transport costs is introduced, the theorem can be revalidated. With transport costs on every commodity, commodity prices would no longer be equal across countries in trade, and therefore factor prices also could not be equalized via commodity price equalization. Thus, while a commodity in the middle of a chain of exportables may be priced out of the export market into being a non-traded good by high transportation costs, it is impossible for it to be turned into an imported good.